2023
DOI: 10.52041/serj.v22i1.77
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-Cognitive Factors in the Introductory Statistics Classroom

Abstract: The study reported in this paper aimed to not only understand student attitudes towards statistics, but also their beliefs about their ability to perform statistical tasks (self-efficacy), the value they place on carrying out course and statistical tasks (task value), and level of effort they perceive when engaging in these tasks (cost) across a semester in an undergraduate introductory statistics course. Findings indicated that students viewed statistics as more difficult, less valuable, and more costly to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In the same line, another research found that anxiety levels and motivation in that order were predictor variables of the performance variable ( Suren and Kandemir, 2020 ). Spencer et al (2023) found that self-efficacy was also a predictor variable of overall course grade. In our study, the results obtained have been confirmed using the fundamentals of a classical methodology based on regression analysis and, especially, with the innovative design of artificial neural networks, which have proven to be very useful in the field of educational psychology ( Hwang et al, 2020 ; Martínez-Ramón et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In the same line, another research found that anxiety levels and motivation in that order were predictor variables of the performance variable ( Suren and Kandemir, 2020 ). Spencer et al (2023) found that self-efficacy was also a predictor variable of overall course grade. In our study, the results obtained have been confirmed using the fundamentals of a classical methodology based on regression analysis and, especially, with the innovative design of artificial neural networks, which have proven to be very useful in the field of educational psychology ( Hwang et al, 2020 ; Martínez-Ramón et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…In this sense, it is important that future teachers are trained to consider not only the cognitive components but also the affective domain so relevant for the teaching/learning process of mathematics as stated in different studies ( García-Suárez et al, 2023 ; Spencer et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations